Temperature dependence of radiation resistance of scintillation detectors based on lead tungstate crystals - Burachas, S.F.; Ippolitov, M.S.; Manko, V.I.; Nikulin, S.A.; Vasiliev, A.N.; Apanasenko, A.L.; Vasiliev, A.N.; Uzunian, A.V.; Tamulaitis, G. (Functional Materials, 2009)
Effect of gamma irradiation on the radiation resistance of detection blocks based on lead tungstate crystals has been studied in +60 to -25°C temperature range. A decrease in the radiation resistance and in the initial light yield recovery rate has been observed at the crystal temperature decrease. For the qualitative interpretation of the experimental results, the cluster model is used that assumes the presence of tungsten oxide clusters in the regular PWO (PbWO₄) matrix. The induced absorption of PWO crystals has been shown to depend on the cluster defect (CD) chemical composition and to be due to its radiation-induced transformation. The temperature dependence of the crystal radiation resistance has been shown to be in correlation with that of the initial CD composition recovery time. Досліджено вплив гамма-опромінення на радіаційну стійкість блоків детектування на основі кристалів вольфрамату свинцю у температурному діапазоні від +60 до -25°С. 3і зниженням температури кристалів спостерігалося збільшення чутливості до опромінення та уповільнення відновлення початкового світловиходу. Для якісної інтерпретації експериментальних результатів використовується кластерна модель, яка припускає наявність кластерів оксидів вольфраму у регулярній матриці PWO (PbWO₄). Показано, що наведене поглинання кристалів PWO залежить від хімічного складу кластерних дефектів (КД) та обумовлено його радіаційно індукованим перетворенням, а температурна залежність радіаційної стійкості кристалів корелює з температурною залежністю часу відновлення початкового складу КД. Изучено влияние гамма-облучения на радиационную стойкость блоков детектирования на основе кристаллов вольфрамата свинца в температурном диапазоне от +60 до -25°С. С понижением температуры кристаллов наблюдалось увеличение чувствительности к облучению и более медленное восстановление начального световыхода. Для качественной интерпретации экспериментальных результатов используется кластерная модель, предполагающая наличие кластеров оксидов вольфрама в регулярной матрице PWO (PbWO₄). Показано, что наведенное поглощение кристаллов PWO зависит от химического состава кластерных дефектов (КД) и обусловлено его радиационно-индуцированным преобразованием, а температурная зависимость радиационной стойкости кристаллов коррелирует с температурной зависимостью времени восстановления начального состава КД.